Unilateral Head Impulses Training in Uncompensated Vestibular Hypofunction - Ana Carolina Binetti; Andrea Ximena Varela; Dana Lucila Lucarelli; Daniel Héctor Verdecchia (Case Reports in Otolaryngology)
The aim of this paper is to report a case of a young woman with unilateral vestibular chronic failure with a poorly compensated vestibuloocular reflex during rapid head rotation. Additionally, she developed migraine symptoms during the treatment with associated chronic dizzy sensations and blurred vision. Her report of blurred vision only improved after she completed a rehabilitation program using fast head impulse rotations towards the affected side for 5 consecutive days. We discuss why we elected this form of treatment and how this method may be useful for different patients.